Optimalisasi Fungsi Pengawasan DPRD Kabupaten Mamasa Dalam Penyelenggaraan Pemerintahan Daerah - Zebua, Kerenhapukh Valentina; Haliawan, Prity Oktora; Simbolon, Sherly Desinta; Sinaga, Marihot Pandapotan; Darmawan, Ivan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out how the DPRD's supervision is carried out towards optimizing the DPRD's supervisory function regarding the administration of regional government in Mamasa Regency. The research method used was a qualitative method, data collection was carried out using library research techniques sourced from book literature, scientific journals, statutory regulations. The results of this research show that the supervisory function carried out by the Mamasa Regency DPRD is in accordance with Law Number 23 of 2014. However, in its implementation, the Mamasa Regency DPRD is still not running optimally because there are still many obstacles in its implementation